2022
DOI: 10.21203/rs.3.rs-1487070/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of Human Adenovirus in children hospitalized with Community-acquired Gastroenteritis under the age of five years

Abstract: Background: Acute gastroenteritis is the major cause of morbidity and mortality among infants and children around the globe. Along with other enteropathogens, human adenoviruses (HadV) are considered a major etiological agent associated with diarrhea in young children. However, information about the epidemiology of adenoviruses in Rawalpindi and Lahore, the two cities of Punjab province, Pakistan is not reported yet.Methods: A total of 384 fecal samples were negative for rotavirus, out of 1082 from a patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our studies showed that the age group from two to five years is the highest percentage in the number of infections, and this corresponds to another study conducted in Egypt, showed that children under five years are more likely to be infected (26). Other studies in Pakistan and Gabon showed that children under five years are more likely to be infected with HAdV (27)(28). The difference between these studies and our results are due to the difference in the geographical location of the study site or the nature of the society and the economic situation of the country in which the study took place or the techniques used to detect the adenovirus and the extent of the efficiency of the researchers' work and these need studies More comprehensive and broader on a global scale.…”
Section: Discussionsupporting
confidence: 89%
“…Our studies showed that the age group from two to five years is the highest percentage in the number of infections, and this corresponds to another study conducted in Egypt, showed that children under five years are more likely to be infected (26). Other studies in Pakistan and Gabon showed that children under five years are more likely to be infected with HAdV (27)(28). The difference between these studies and our results are due to the difference in the geographical location of the study site or the nature of the society and the economic situation of the country in which the study took place or the techniques used to detect the adenovirus and the extent of the efficiency of the researchers' work and these need studies More comprehensive and broader on a global scale.…”
Section: Discussionsupporting
confidence: 89%